The glucocorticoid receptor interferes with progesterone receptor-dependent genomic regulation in breast cancer cells - Ogara, Maria Florencia (2019)
The glucocorticoid and progesterone receptors (GR and PR) are closely related members of the steroid receptor family. Despite sharing similar structural and functional characteristics; the cognate hormones display very distinct physiological responses. In mammary epithelial cells, PR activation is associated with the incidence and progression of breast cancer, whereas the GR is related to growth suppression and differentiation. Despite their pharmacological relevance, only a few studies have compared GR and PR activities in the same system. Using a PR+/GR+ breast cancer cell line, here we report that either glucocorticoid-free or dexamethasone (DEX)-activated GR inhibits progestin-dependent gene expression associated to epithelial-mesenchymal-transition and cell proliferation. When both receptors are activated with their cognate hormones, PR and GR can form part of the same complex according to co-immunoprecipitation, quantitative microscopy and sequential ChIP experiments. Moreover, genome-wide studies in cells treated with either DEX or R5020, revealed the presence of several regions co-bound by both receptors. Surprisingly, GR also binds novel genomic sites in cells treated with R5020 alone. This progestin-induced GR binding was enriched in REL DNA motifs and located close to genes coding for chromatin remodelers. Understanding GR behavior in the context of progestin-dependent breast cancer could provide new targets for tumor therapy.